Konflik Pelimpahan Aset Tidak Bergerak Daerah Induk kepada Daerah Otonom Baru sesuai Undang-Undang Nomor 5 Tahun 1996 tentang Pembentukan Daerah Kotamadya Tingkat II Kupang - Sirilus N M Lelan (Jurnal Inovasi Kebijakan, 2018)
In accordance with the mandate of Law Number 5 of 1996 concerning the Establishment of the Regional Level II Kupang Municipality, the delegation of immovable assets to the new autonomous region, namely the Regional Government of Kupang city must be carried out for a period of one year. However, in fact until now the delegation or handover of assets to new autonomous regions has not been submitted. Conflicts that arise between these two regions, can’t be denied, the longer it happens will become more protracted if it is not immediately resolved as soon as possible. And the problem in this study is that why has the District Government not handed over immovable assets to the Kupang City Regional Government yet ? To answer the problems studied, the researcher conducted document collection and interviews with several parties. The results of the study show that there are still many immovable assets that have not been submitted or transferred to new autonomous regions. This is because the parent region must shift or move from its territory and build a location in the new area, the strategic assets that become the source of income for the area become lost by itself.